Possibility of using fatty acid profiles for the authentication of beef adulterated with pork, donkey, and dog meat - Elsabagh, Rasha; Abdeen, Ahmed; K. Morsy, Mohamed; M. Rayan, Ahmed; A. Abdelrahman, Elsayed; AbdElaaty, Elsayed M.; F. Ibrahim, Samah; Abdelkhalek, Adel; Șmuleac, Laura; Fericean, Liana; Elgazzar, Ahmed; M. El-Sayed, Amal; et al. (Italian Journal of Food Science, 2024)
Detection of meat adulteration is a critical issue in food labeling procedures and a serious concern related to food fraud, authenticity, and religious beliefs. The current work detected and quantified adulteration of raw ground beef with pork, donkey, and dog meat based on fatty acid profiles using GC-MS/MS. The study design incorporated pork, donkey, or dog meat with beef meat; negative and positive controls were used for the different meat species. Results demonstrated several significant differences (p < 0.05) in fatty acid contents between mixed/adulterated meat and pure beef. In addition, higher total saturated fatty acid levels in ground beef (57.91%) compared to dog fat (46.44%), donkey (38.71%), and pork fat (lard) (40.23%). High total unsaturated fatty acids content was observed in donkey (61.92%), pork (59.77%), and dog (53.56%) fats compared to beef fat (42.09%). On the other hand, total unsaturated and monounsaturated fatty acids in beef meat were lower than in pork, donkey, and dog meat. Moreover, the highest trans-fatty acid content was found in pork compared to the other meat types. All incorporated samples correlated positively with pure ground beef concerning the fatty acid profiles. Therefore, alteration of the mixed beef fatty acid profiles was a potential indicator for adulteration since a marked decrease in total saturated fatty acid content and an increase in unsaturated fatty acids was observed in the substituted samples. We concluded that GC-MS/MS-based fatty acid profiling is a promising technique that can be used to detect meat adulteration.